Molecular Detection and Genotypic Study of Leptotrichia SPP by 16SrRNA Gene that Isolated from Bacterial Vaginosis Miscarriage and Non-miscarriage Women in AL-hillah City - A. Bunyan, Ilham; K. Hameed, Alaa; K. Gatea, Asmaa (International Journal of Psychosocial Rehabilitation, 2020)
This study was aimed at determining Leptotrichia spp. by a culture-independent method from both bacterial vaginosis women without miscarriage and vaginosis women with miscarriage. Also, another aim was sequencing of the 16SrRNA gene was conducted for phylogenetic tree study of local isolates of Leptotrichia spp. in comparison to world Leptotrichia spp. isolates in NCBI GenBank and lastly deposition of the current isolates in GenBank. One hundred fifty (150) high vaginal swabs were collected from women with vaginosis (seventy-five samples were taken from married women with vaginosis without miscarriage and seventy-five samples from women with vaginosis with miscarriage) from Babylon City Hospital and private clinics. The age of the patient is 15–45 years. The sample was collected by disposable swabs, and 16s rRNA gene detection was done by the polymerase chain reaction technique. Results revealed that 63 (84.00%) and 42 (56.00%) of Leptotrichia spp. out of 150 swabs obtained by PCR from miscarriage and non-miscarriage vaginosis women, respectively. A phylogenetic study of the 16S rRNA gene indicated that local Leptotrichia spp. (NO. 1 and NO. 2) isolates shared higher homology with other Leptotrichia spp. isolates available in the GenBank. The homology of the nucleotides was between 99.06% for both isolates.